Scrotal exploration for suspected testicular torsion in adolescents and adults: analysis of a series of 135 cases - Brahima Kirakoya; Clotaire Yameogo; Morgane Kambou; Ouedan Idogo; Abdullah Ayed; Gille Nacthagande; Fasnewinde Aristide Kabore (African Journal of Urology)
Abstract Background Testicular torsion (TT) is the abnormal twisting of the spermatic cord leading to strangulation of the testis. Any non-traumatic acute scrotal pain in adolescents and young adults is considered TT until proven otherwise. It is a urological emergency. The diagnosis is clinically based on symptoms and signs that raise a high index of suspicions. Scrotal exploration is necessary, which will provide diagnostic certainty and allow treatment. Methods This study aimed to assess the clinical predictors of TT. This was a retrospective cross-sectional study of patients aged 15 years and older who underwent surgical exploration for suspected TT from January 2005 to December 2021 at Teaching Hospital Yalgado Ouedraogo (Burkina Faso). We compared the demographic data and clinical findings of patients according to the intraoperative diagnosis. Results In total, 135 scrotal explorations were performed for suspected TT. The average age of the patients was 24.56 years. TT was found in 123 cases (91.11%), epididymo-orchitis in 8 cases (5.93%) and in 4 cases (2.96%) no abnormality was found. Scrotal swelling and elevation of the testicle were more common in TT than in other cases (p < 0.001 in both cases). Fever was more frequent when it was not a TT (p < 0.001). Scrotal Doppler ultrasound had a sensitivity of 91%. The orchiectomy rate was 60.16% (N = 74) in patients with TT. Conclusion The clinical findings based on scrotal pain and swelling, elevation of the testicle and the absence of fever are sufficient to suggest TT and to perform surgical exploration.